Implementasi TIK Dalam Meningkatkan Efektifitas Kegiatan Belajar Mengajar dan Administrasi Di Sekolah: Studi Kasus Di PAUD Mustika Desa Budug Kecamatan Kwadungan Kabupaten Ngawi - Suwartiningsih Suwartiningsih (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2021)
Early Childhood Education (PAUD) is a coaching effort aimed at children from birth up to the age of six which is carried out through the provision of educational stimuli, as a form of assistance for physical and spiritual growth and development so that children are ready to enter further education. The low expertise and professionalism of teachers, limited infrastructure and learning tools have a negative impact on the learning process. In line with global developments, Islamic schools face quite basic managerial challenges. The hope from various parties that education is managed with a modern education management pattern is one of the developments that have emerged in the current competitive era. This study aims to describe the extent to which the implementation of ICT in PAUD Mustika, Budug Village, Kwadungan District, Ngawi Regency, is related to increasing the effectiveness of teaching and learning activities and administrative activities. The results of this study are: (1) Implementation of ICT-based learning in Mustika PAUD, Budug Village, Kwadungan District, Ngawi Regency, namely: a) Curriculum field, b) Learning strategy area, c) Learning material, d) Assessment. (2) The impact of ICT implementation in increasing the effectiveness of teaching and learning activities and administration includes: a) Competitive advantage strategy; b) Learning is more effective and efficient; c) Simplify the management of school administrative management data; d) Performance productivity increases because the system used is digital based.